"Heat and Mass Transfer, (SI Units) (For B.E / B.Tech, I.E.S and I.A.S Examinations)" - Yadav (R); Sanjay; Rajay ("18-C, Sarojoni Naidu MargAllahabad", 2004)
Heat and Mass Transfer
Keywords: Heat and Mass Transfer